2020
DOI: 10.1158/2159-8290.cd-19-0710
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic Subclones Confer Resistance to Venetoclax-Based Therapy in Patients with Acute Myeloid Leukemia

Abstract: Venetoclax-based therapy can induce responses in approximately 70% of older previously untreated patients with acute myeloid leukemia (AML). However, upfront resistance as well as relapse following initial response demonstrates the need for a deeper understanding of resistance mechanisms. In the present study, we report that responses to venetoclax + azacitidine in patients with AML correlate closely with developmental stage, where phenotypically primitive AML is sensitive, but monocytic AML is more resistant.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
351
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(412 citation statements)
references
References 49 publications
(65 reference statements)
21
351
2
Order By: Relevance
“…2B-2C). Interestingly and as opposed to previously reported treatment with VEN+AZA 49 To investigate the mechanism of cell death induced by this duplet therapy VEN+AraC, we treated AML cells exposed to VEN+AraC or single agents with the irreversible pan-caspase inhibitor Z-VAD-FMK that prevents apoptosis by blocking initiator caspases (such as caspase-2, -8, -9, and -10) and executioner/effector caspases (caspase-3, -6, and -7) 55 . We showed that Z-VAD-FMK rescued not only OCR, but also mitochondrial calcium, loss of related to calcium ion homeostasis ( Supplementary Fig.…”
Section: Oxphos-dependent Resistance Of Aml Cells To Cytarabinecontrasting
confidence: 90%
“…2B-2C). Interestingly and as opposed to previously reported treatment with VEN+AZA 49 To investigate the mechanism of cell death induced by this duplet therapy VEN+AraC, we treated AML cells exposed to VEN+AraC or single agents with the irreversible pan-caspase inhibitor Z-VAD-FMK that prevents apoptosis by blocking initiator caspases (such as caspase-2, -8, -9, and -10) and executioner/effector caspases (caspase-3, -6, and -7) 55 . We showed that Z-VAD-FMK rescued not only OCR, but also mitochondrial calcium, loss of related to calcium ion homeostasis ( Supplementary Fig.…”
Section: Oxphos-dependent Resistance Of Aml Cells To Cytarabinecontrasting
confidence: 90%
“…Moreover, drug synergy from combining BCL2 and MCL1 inhibitors can be achieved across all subtypes and mutational profiles of MDS in this model, even in the presence of RAS family mutations that are thought to confer resistance to VEN monotherapy (eg. CBL and PTPN11 in this cohort) [14][15][16][17][18] . 38 and in vivo 11 is limited at clinically meaningful doses.…”
Section: Discussionmentioning
confidence: 72%
“…The data presented here suggest dual BCL2+MCL1 inhibition may be considered for the treatment of all MDS subtypes regardless of mutational status, even those with mutations that may be less likely to respond to VEN monotherapy (eg. TP53 or RAS family mutations) [14][15][16][17][18] MLD is multi-lineage dysplasia; EB1 is excess blasts 5-9%; EB2 is 10-19% blasts; CFU-GEMM is colony-forming unit -granulocyte, erythroid, macrophage, megakaryocyte; CFU-GM is colony-forming unit -granulocyte, macrophage; BFU-E is burst-forming unit -erythroid. n/a n/a n/a n/a n/a n/a n/a DNMTi x12 n/a DNMTi x4 DNMTi x5 DNMTi x1 DNMTi x16 DNMTi x16 n/a n/a DNMTi x3 n/a n/a n/a DNMTi x5 IMID x2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-targeted therapies provide an opportunity for synergistic inhibition of multiple resistance mechanisms, including patient-specific cancer rescue pathways and phenotypic redundancy across heterogeneous cancer subclones [8][9][10][11][12][13] . However, the emergence of resistance is a dynamic process influenced by both genetic and molecular factors, together with selective pressure from the administered therapeutics; this can be seen for example in the emergence of NRAS-mutated subclones in the acquired resistance to FLT3 inhibition, 7 or intrinsic molecular and metabolic properties of monocytic subclones of patient cells resistant to venetoclax therapy 14 .…”
Section: Introductionmentioning
confidence: 99%